Identification of genes required for Pseudomonas aeruginosa carnitine catabolism - Wargo, Matthew J. (Microbiology Society, 2009)
Carnitine is a quaternary amine compound prevalent in animal tissues, and a potential carbon, nitrogen and energy source for pathogens during infection. Characterization of activities in Pseudomonas aeruginosa cell lysates has previously shown that carnitine is converted to 3-dehydrocarnitine (3-dhc) which is in turn metabolized to glycine betaine (GB), an intermediate metabolite in the catabolism of carnitine to glycine. However, the identities of the enzymes required for carnitine catabolism were not known. We used a genetic screen of the P. aeruginosa PA14 transposon mutant library to identify genes required for growth on carnitine. We identified two genomic regions and their adjacent transcriptional regulators that are required for carnitine catabolism. The PA5388–PA5384 region contains the predicted P. aeruginosa carnitine dehydrogenase homologue along with other genes required for growth on carnitine. The second region identified, PA1999–PA2000, encodes the α and β subunits of a predicted 3-ketoacid CoA-transferase, an enzymic activity hypothesized to be involved in the first step of deacetylation of 3-dhc. Furthermore, we confirmed that an intact GB catabolic pathway is required for growth on carnitine. The PA5389 and PA1998 transcription factors are required for growth on carnitine. PA5389 is required for induction of the PA5388–PA5384 transcripts in response to carnitine, and the PA1999–PA2000 transcripts are induced in a PA1998-dependent manner and induction appears to depend on a carnitine catabolite, possibly 3-dhc. These results provide important insight into elements required for carnitine catabolism in P. aeruginosa and probably in other bacteria.